Development of siRNA-Based Therapeutic Strategy Targeting Virulence Factor lpfA of Zoonotic Escherichia coli O157:H7 - Rian Ka Praja; Oktaviani Naulita Turnip; Hanasia Hanasia; Reny Rosalina (Biology, Medicine, & Natural Product Chemistry, 2026)
This study aimed to identify potential small interfering RNA (siRNA) molecules capable of silencing the lpfA virulence gene of Escherichia coli O157:H7, a zoonotic pathogen responsible for severe gastrointestinal disease. The nucleotide sequence of lpfA from E. coli O157:H7 strain Sakai was analyzed, and candidate siRNAs were designed using multiple bioinformatics tools, including siPRED, siRNA Scales, MaxExpect, and DuplexFold. Top ten selected siRNA candidates demonstrated high predicted inhibitory activity, with silencing efficiencies ranging from 93.73% to 94.66%. Secondary structure predictions indicated stable folding without inhibitory intramolecular structures, while binding energy analysis showed strong siRNA–mRNA duplex stability, with the best candidate exhibiting -26.5 kcal/mol. These findings suggest that the identified siRNAs possess strong theoretical potential to suppress lpfA expression and may serve as candidates for future experimental validation. Overall, this study provides a foundational step toward developing siRNA-based therapeutic strategies targeting key virulence factors of E. coli O157:H7.